Avalia????o do sistema de gerenciamento de res??duos de servi??os de sa??de - Campos, Fabiana dos Santos Pereira (2015)
The objective of the research was to evaluate the performance of management of health care waste systems in hospitals organizations, in view of their managers. Indicators were created and developed a performance evaluation tool for the management of healthcare waste integrated with environmental management systems, occupational health and safety; to further identify the predominant model RSS management in each organization investigated. We used the method of multiple case study, through exploratory research, qualitative in nature. The main sources of evidence in the triangulation of data were: a semi-structured interview and the identification form the predominant model for assessing the RSS management systems in the hospital; structured questionnaires; documentary research, and direct non-participant observation conducted in selected health organizations. There was a content analysis, which had the category and subcategory dimensions (operational, administrative, environmental and financial) and parameters of the assessment tool proposed. The results indicated that all hospitals need improvement. The operational dimension presented greater relevance, while the financial dimension is the lowest maturity by limitations on resources. All hospitals investigated were classified as organizations with an RSS management, but need improvement. The RSS management goes beyond the implementation of an ideal management system for the proper management of RSS, as it is also necessary that the individual has commitment and values of citizenship and ethics, responsibility and solidarity in the exercise of their daily activities in this process. It is believed that this evaluation can help improve the GRSS, serving as instrumental for managers assess the management system of the RSS, with the support of prevailing models, favoring strategic decisions to improvements in all worked dimensions in an integrated way.